2016
DOI: 10.1016/j.jtcvs.2016.07.070
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive-ventilation-renal score reliably predicts hospital length of stay after surgery for congenital heart disease

Abstract: Objectives: We aimed to further validate the vasoactive-ventilation-renal score as a predictor of outcome in patients recovering from surgery for congenital heart disease. We also sought to determine the optimal time point within the early recovery period at which the vasoactive-ventilation-renal score should be measured. Methods: We prospectively reviewed consecutive patients recovering from cardiac surgery within our intensive care unit between January 2015 and June 2015. The vasoactive-ventilation-renal sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 14 publications
4
42
0
Order By: Relevance
“…In the most recent single center VVR study, a VVR score greater than 25 was identified as the best cutoff point distinguishing between children who were at risk for poor postoperative outcome and children who were not (10). Not surprisingly, in a cohort of patients that included only neonates, who tend to be more complex (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the most recent single center VVR study, a VVR score greater than 25 was identified as the best cutoff point distinguishing between children who were at risk for poor postoperative outcome and children who were not (10). Not surprisingly, in a cohort of patients that included only neonates, who tend to be more complex (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The vasoactive-ventilation-renal (VVR) score is a novel disease severity index that incorporates validated markers of cardiovascular, pulmonary, and renal function. In single center studies, it has been shown to be a robust predictor of outcomes in heterogenous populations of children recovering from surgery for congenital heart disease (8)(9)(10). These studies have included neonates (8)(9)(10), children with cyanotic congenital heart disease (9)(10), children undergoing cardiopulmonary bypass (8)(9)(10), children not undergoing cardiopulmonary bypass (9)(10), and adults with congenital heart disease (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…genital heart disease group during their pediatric ICU stay [3][4][5]. The basic desired features of all these scoring systems are to build a reliable system that is available in common and decrease ICU costs, the efficient use of the sources, to be guiding in clinical decisions and practices and allow objective evaluation.…”
mentioning
confidence: 99%
“…Prospective validation by Miletic and colleagues in a heterogeneous population of pediatric patients undergoing cardiac surgery found the 48-h VVR score to be a predictor of outcomes and outperformed VIS [3]. Prolonged hospital LOS was predicted by the VVR at 12 hours in another prospective study by Scherer et al of a heterogeneous population of patients undergoing congenital heart surgery [4]. Multicenter validation of the score in neonatal cardiac surgery is ongoing [5].…”
Section: Introductionmentioning
confidence: 99%